An Analysis of Women’s Language Features Used by the Indonesian Female Podcasters - Novita Sari, Yesi; Hendi Pratama; Fahrur Rozi (English Education Journal, 2024)
This research aimed to explain the teacher's reflection and students' perception regarding the Use of Technology to Promote Students' Engagement in English Class at SMA Negeri 3 Demak in 2024/2025 Academic Year.  The design of this research is qualitative research. In collecting data, the researcher used questionnaires and interviews. The students filled out the questionnaire to fulfill the students' engagement about using technology in the English class, supported by the open question interview from the English teacher and students of SMA Negeri 3 Demak. The sample of this research is the eleventh grade with 32 students.  The research used random sampling to decide the research sample. This study's result revealed that technology can improve the student's engagement in English class. The findings indicate that when effectively implemented, technology enhances students' engagement by providing interactive and personalized learning experiences. Overall, the research highlights that the use of technology can transform educational practices and improve learning outcomes while emphasizing the importance of learning to ensure equitable access and benefits for all students. The findings and discussion showed that the use of technology makes students engaged, pay attention, interested, motivated, focus, have fun, actively participate, understand the material, interact with each other, enjoy, like, interact, develop their ability, improve communication skill, enhance, and enthusiasm